SOCIAL TRANSFORMATION THROUGH THE KKN PROGRAM UIN SUMATERA UTARA - Khairi, Muhammad Galih; Mutiara, Tia; Azhar, Azhar; Dharmawan, Muhamad Dhimas (PERSPEKTIF: Journal of Social and Library Science, 2024)
Social transformation is a process of fundamental but significant changes that occur in social structures, interaction patterns, norms values, and institutions in a society. Social transformation can occur due to several important factors, one of which is education. Increased access and quality in education can empower individuals and groups to demand social change in a more positive direction and play a more active role in society. This action researchers do as a form of problem solving that occurs in the village of Lalang, Tanjung Pura District, Langkat Regency where the local community is still less concerned about the importance of non-formal education. Non-formal education needs to be applied to this village because of the many problems that occur such as low interest in learning, poor literacy levels and interest in reading, lack of community potential in career development, and so on. This research was conducted using a qualitative approach and descriptive method, where researchers collected data from various sources such as observation, interviews, and documentation. The various programs carried out in the implementation of non-formal education provide positive results and impacts for the community and researchers. The increasing enthusiasm and concern of the community about the importance of non-formal education has shown that the success in social transformation is being carried out.